2019
DOI: 10.1042/bst20190563
|View full text |Cite
|
Sign up to set email alerts
|

Editor's cut: DNA cleavage by CRISPR RNA-guided nucleases Cas9 and Cas12a

Abstract: Discovered as an adaptive immune system of prokaryotes, CRISPR–Cas provides many promising applications. DNA-cleaving Cas enzymes like Cas9 and Cas12a, are of great interest for genome editing. The specificity of these DNA nucleases is determined by RNA guides, providing great targeting adaptability. Besides this general method of programmable DNA cleavage, these nucleases have different biochemical characteristics, that can be exploited for different applications. Although Cas nucleases are highly promising, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 108 publications
(172 reference statements)
2
15
0
Order By: Relevance
“…From the occupation probabilities, we can also suggest a simple free energy diagram for the different states (Figure 2h). The S1, S2 and S3 states could correspond to the previously identified conformation checkpoints that couple R-loop propagation to nuclease activation [8]. The linker and lid interactions may produce the occupancy of the S1 and S2 states, respectively.…”
Section: Single Molecule Observation Of Dynamic R-loops and Downstream Dna Breathingmentioning
confidence: 84%
See 4 more Smart Citations
“…From the occupation probabilities, we can also suggest a simple free energy diagram for the different states (Figure 2h). The S1, S2 and S3 states could correspond to the previously identified conformation checkpoints that couple R-loop propagation to nuclease activation [8]. The linker and lid interactions may produce the occupancy of the S1 and S2 states, respectively.…”
Section: Single Molecule Observation Of Dynamic R-loops and Downstream Dna Breathingmentioning
confidence: 84%
“…A key difference between Type II-A and Type V-A CRISPR-Cas effectors is that the former use two separate nuclease domains to cut the NTS and TS while the latter use a single RuvC domain that must transition sequentially between the NTS and TS (8). It has been suggested that R-loop asymmetry is exploited by Cas12a to allow downstream DNA breathing that is a key step in providing the single strand TS that can be delivered to the RuvC nuclease active site (30).…”
Section: A Stable Downstream Dna Clamp State Following Non-target Strand Cleavagementioning
confidence: 99%
See 3 more Smart Citations